2023
DOI: 10.1038/s41467-023-40441-4
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric G-quadruplex motifs-induced NFRs determine strong replication origins in vertebrates

Abstract: Replication of vertebrate genomes is tightly regulated to ensure accurate duplication, but our understanding of the interplay between genetic and epigenetic factors in this regulation remains incomplete. Here, we investigated the involvement of three elements enriched at gene promoters and replication origins: guanine-rich motifs potentially forming G-quadruplexes (pG4s), nucleosome-free regions (NFRs), and the histone variant H2A.Z, in the firing of origins of replication in vertebrates. We show that two pG4s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Recently, a new functional genetic element, pG4s, associated with specific nucleosome-free regions (NFRs), was found to be sufficient for replication initiation. The authors suggested that this might be a strategy for the ORC recognition of origins in eukaryotes [ 80 ].…”
Section: Chromatin Governs the Spatiotemporal Dynamics Of Pre-rc Factorsmentioning
confidence: 99%
“…Recently, a new functional genetic element, pG4s, associated with specific nucleosome-free regions (NFRs), was found to be sufficient for replication initiation. The authors suggested that this might be a strategy for the ORC recognition of origins in eukaryotes [ 80 ].…”
Section: Chromatin Governs the Spatiotemporal Dynamics Of Pre-rc Factorsmentioning
confidence: 99%